2019
DOI: 10.1111/phn.12620
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Children Growth and Development: A community‐based cluster randomized controlled trial in rural areas of Indonesia

Abstract: Objective: This study examined the influence of the Promote Children's Growth and Development (PCGD) intervention on children's growth and development in rural areas in Indonesia. Design and Sample: A community-based nonblinded cluster randomized controlled trial was conducted. Twelve clusters of villages were matched based on population and randomly assigned to intervention group (six clusters and 72 caregivers dyads) or control group (six clusters and 72 caregivers dyads) with inclusion criteria age 0-72 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
2
10
2
2
Order By: Relevance
“…Furthermore, this study showed that mother's work, children's age, and weight of birth influenced CD 3 months old infants, which were similar to previous studies 14,32 . Also, relationship factor was also observed to influence CD among 6 months old infants.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, this study showed that mother's work, children's age, and weight of birth influenced CD 3 months old infants, which were similar to previous studies 14,32 . Also, relationship factor was also observed to influence CD among 6 months old infants.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, monitoring the condition of infants and maternal characteristics of breastfeeding mothers is very necessary, in order to support the sustainability of EBP. Also, observations showed that children's age and height influenced NCS (underweight and stunting), especially weight of birth, which were similar to previous studies 14,32 . Also, infant temperament (including approach and attentional shifting) was observed to influence underweight among 6 months old children.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Data from the national health survey also showed that the age group of 26-35 years was the largest labor force group in Indonesia compared to other age groups. This age group was also called the productive period, where a person had high energy, creativity, and productivity [17].…”
Section: Discussionmentioning
confidence: 99%